Pharmacodynamic modelling and exposure–response assessment of inebilizumab in subjects with neuromyelitis optica spectrum disorders. Issue 8 (5th April 2022) - Yan, Li; Wang, Bing; She, Dewei; Mitchell, Ben; Criste, Ryan; Cimbora, Daniel; Katz, Eliezer; Rees, William A.
Abstract : Aims: Neuromyelitis optica spectrum disorders (NMOSD) is an autoantibody‐mediated, B cell‐driven disease. Inebilizumab is a humanized, affinity‐optimized, afucosylated IgG1 κ monoclonal antibody that binds to the B‐cell specific surface antigen CD19, resulting in rapid, profound and sustained depletion of circulating peripheral B cells in NMOSD subjects (pivotal study). The objective of this study was to conduct population modelling of B‐cell response following inebilizumab treatment in adult subjects with NMOSD, and to assess the impact of drug exposure to outcome. Methods: A haematopoietic transit model was developed to describe the joint effects of reducing influx from pro‐B cells and accelerating CD20 + B‐cell depletion in the blood by inebilizumab. Furthermore, the relationships between inebilizumab pharmacokinetic (PK) exposure and the primary efficacy endpoint and key secondary efficacy endpoints were evaluated. Results: At the 300‐mg dose, there was no apparent relationship between efficacy (reduction in disease attack risk, risk of worsening from baseline in Expanded Disability Status Scale, cumulative total active MRI lesions, and the number of NMOSD‐related in‐patient hospitalizations) and PK exposure. Subjects with low, medium and high PK exposure had a similar hazard ratio of NMOSD attack vs . placebo group. Conclusion: The pharmacodynamic modelling confirmed effective depletion of B cells is achieved with a 300 mg intravenous dose of inebilizumab administered on Day 1 and Day 15 and every 6 months thereafter. The PK variability between patients had no apparent effect on clinical efficacy.